Epstein–Barr Virus-Associated Malignancies: Roles of Viral Oncoproteins in Carcinogenesis - El-Sharkawy, Ahmed; Al Zaidan, Lobna; Malki, Ahmed (Frontiers in Oncology, 2018)
The Epstein-Barr virus (EBV) is the first herpesvirus identified to be associated with human cancers known to infect the majority of the world population. EBV-associated malignancies are associated with a latent form of infection, and several of the EBV-encoded latent proteins are known to mediate cellular transformation. These include six nuclear antigens and three latent membrane proteins. In these lymphoid and epithelial tumours, viral latent gene expressions have distinct pattern. In both primary and metastatic tumors, the constant expression of latent membrane protein 2A (LMP2A) at the RNA level suggests that this protein is the key player in the EBV-associated tumorigenesis. While LMP2A contributing to the malignant transformation possibly by cooperating with the aberrant host genome. These can be done in part by dysregulating signalling pathways at multiple points, notably in the cell cycle and apoptotic pathways. Recent studies also have confirmed that LMP1 and LMP2 contribute to carcinoma progression and that this may reflect the combined effects of the proteins on activation of multiple signaling pathways. This review article aims to investigate the aforementioned EBV encoded proteins that reveal established roles in tumour formation, with a greater emphasis on the oncogenic Latent Membrane Proteins (LMP1, LMP2A) and their roles in dysregulating signalling pathways. It also aims to provide a quick look on the six members of the EBV Nuclear Antigens (EBNAs) and their roles in dysregulating apoptosis.